Interdisziplinäre Kompetenz in der Wirtschaft = Interdisciplinary competency in business - Brandstädter, Simone; Schleiting, Yannick; Sonntag, Karlheinz (Zeitschrift für Arbeitswissenschaft, 2018)
Individual team members’ competences play an important role in the success of interdisciplinary projects. By means of expert interviews, this study surveyed whether the “Interdisciplinary Competency” model, which was developed in a research context, is also valid in a business context. A comparison of expert assessments of proficiency levels required for business and research sectors showed only moderate difference. Most individual competencies were rated slightly higher in the business sample. The results demonstrate the significance of the specified competency areas with good reliability and thus support using the model in a business context. Practical Relevance: In order to reap the benefits of multi-functional teams, it is necessary to consider the (cognitive, social, communicative) skills and abilities or traits of individual team members. As this study shows, competencies that are relevant for successful interdisciplinary collaboration are valid in the corporate sector as well. Therefore, the “Interdisciplinary Competency” model can be applied in an organizational context as a theoretical framework for employee selection, development or work design.
Online publiziert: 11. Oktober 2017
Gesehen am 29.07.2019